2008
DOI: 10.7326/0003-4819-149-8-200810210-00009
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in Primary Care to Promote Breastfeeding: An Evidence Review for the U.S. Preventive Services Task Force

Abstract: Evidence suggests that breastfeeding interventions are more effective than usual care in increasing short- and long-term breastfeeding rates. Combined pre- and postnatal interventions and inclusion of lay support in a multicomponent intervention may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
195
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(208 citation statements)
references
References 124 publications
4
195
3
6
Order By: Relevance
“…Evidenciou-se elevada adesão à prática do aleitamento materno durante a permanência do binômio mãe-bebê na maternidade 23 , havendo maior necessidade de se investir no apoio à dupla após a sua alta 24 . Vários países, como Chile, Peru, Nicarágua, Argentina e Reino Unido, desenvolveram passos para o incentivo ao aleitamento materno na atenção primária 25 , e estudos apontam que ações desenvolvidas durante o pré-natal e no período pós-natal são capazes de aumentar, de forma significativa, as prevalências de aleitamento materno 25,26 .…”
Section: Discussionunclassified
“…Evidenciou-se elevada adesão à prática do aleitamento materno durante a permanência do binômio mãe-bebê na maternidade 23 , havendo maior necessidade de se investir no apoio à dupla após a sua alta 24 . Vários países, como Chile, Peru, Nicarágua, Argentina e Reino Unido, desenvolveram passos para o incentivo ao aleitamento materno na atenção primária 25 , e estudos apontam que ações desenvolvidas durante o pré-natal e no período pós-natal são capazes de aumentar, de forma significativa, as prevalências de aleitamento materno 25,26 .…”
Section: Discussionunclassified
“…We included a total of six case-control studies [167][168][169][170][171][172] and five cohort studies 165,[173][174][175][176] that examined the risk of fractures in relation to a history of breastfeeding (Table 25). The casecontrol studies included 1,609 cases with hip, forearm, or vertebral fractures and 2,967 controls.…”
Section: Characteristicsmentioning
confidence: 99%
“…[6][7][8] Women will benefit from moderated group discussions, group prenatal visits, systematic case management, or referral to a lay support organization prior to delivery. [6][7][8]12 There is also good evidence that peer counseling promotes the initiation and maintenance of breastfeeding. 15,16 (I, II-3, III)…”
Section: Prenatalmentioning
confidence: 99%
“…All pregnant women must receive education about the benefits and management of breastfeeding to allow an informed decision about infant feeding. [5][6][7][8][9][10] An evidence-based review of practices that improve the duration or initiation of breastfeeding found that ''prenatal combined with postnatal interventions are more effective than usual care in prolonging the duration of breastfeeding..'' 12 Information and advice from a health professional early in pregnancy are also supported by the American College of Obstetricians and Gynecologists and the American Academy of Family Physicians in their policy statements, which read ''Advice and encouragement of the obstetrician-gynecologist are critical in making the decision to breastfeed'' 6 and ''Family-centered care (the belief that health care staff and the family are partners, working together to best meet the needs of the patient) allows support of breastfeeding practices throughout the lifecycle to all family members.'' 9 (I, II-1, II-2, II-3, III) 2.…”
Section: Prenatalmentioning
confidence: 99%